KONSEP DAN PERKEMBANGAN EKONOMI ISLAM PADA MASA TURKI USMANI - Khisan, Zariatul; Novita, Della; Maymunah, Noor; NKoso, Nur Auliani; Hidayati, Tri; Maftukhatusolikhah, Maftukhatusolikhah (Institut Agama Islam Negeri Kerinci, 2024)
Purpose: The purpose of this study is to analyze the development of the Islamic economy during the Ottoman Empire. Design/methodology/approach: The research method used in this research is library research. The data used is secondary data obtained from relevant sources, books, journals and so on. Findings: Ottoman Türkiye paid more attention to progress in the political and military fields. In this way, economic and financial conditions contributed to the development of Islam in the Ottoman Empire. Islamic economics during the Ottoman Empire reflected the integration of Islamic economic principles with practical economic practices and effective administration. So, according to researchers of the Ottoman Empire, it is very interesting to study in order to find out how the concept and development of Islamic economics was during the Ottoman Empire. Research implications: The implications of the development of the Islamic economy during the Ottoman Empire include:Expansion of Trade Networks: The Ottoman Empire's strategic location bridged East and West, facilitating extensive trade networks that promoted economic growth and cultural exchange.